Production of Chlorella vulgaris as a source of essential fatty acids in a tubular photobioreactor continuously fed with air enriched with CO2 at different concentrations. (14th March 2014) - Ortiz Montoya, Erika Y.; Casazza, Alessandro A.; Aliakbarian, Bahar; Perego, Patrizia; Converti, Attilio; de Carvalho, João C. Monteiro
<x xml:space="preserve">Abstract</x> To reduce CO2 emissions and simultaneously produce biomass rich in essential fatty acids, Chlorella vulgaris CCAP 211 was continuously grown in a tubular photobioreactor using air alone or air enriched with CO2 as the sole carbon source. While on one hand, nitrogen‐limited conditions strongly affected biomass growth, conversely, they almost doubled its lipid fraction. Under these conditions using air enriched with 0, 2, 4, 8, and 16% (v/v) CO2, the maximum biomass concentration was 1.4, 5.8, 6.6, 6.8, and 6.4 gDB L−1 on a dry basis, the CO2 consumption rate 62, 380, 391, 433, and 430 <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghtb2m03t" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />mgCO2</alternatives> L−1 day−1, and the lipid productivity 3.7, 23.7, 24.8, 29.5, and 24.4 mg L−1 day−1, respectively. C. vulgaris was able to grow effectively using CO2‐enriched air, but its chlorophyll a (3.0–3.5 g 100gDB−1), chlorophyll b (2.6–3.0 g 100gDB−1), and lipid contents (10.7–12.0 g 100gDB−1) were not significantly influenced by the presence of CO2 in the air. Most of the fatty acids in C. vulgaris biomass were of the saturated series, mainly myristic, palmitic, and stearic acids, but a portion of no less than 45% consisted of unsaturated fatty acids, and about 80% of these were high added‐value essential fatty acids belonging to the ω3 and ω6 series. These results highlight that C. vulgaris biomass could be of great importance for human health when used as food additive or for functional food production. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:916–922, 2014